2006
DOI: 10.1007/s00436-006-0366-x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of protoscoleces and AgB from Echinococcus granulosus on human neutrophils: possible implications on the parasite’s immune evasion mechanisms

Abstract: The factors affecting the innate susceptibility to Echinococcus granulosus infections are largely unknown. We assessed the interaction of healthy human neutrophils with protoscoleces (PSC) and antigen B (AgB) of E. granulosus by analysis of CD11b upregulation and H(2)O(2) production by flow cytometry. PSC induced neutrophil activation, but their viability was not affected. In contrast, no effects were observed with AgB in both assays. Neutrophil-enriched fractions were also incubated with PSC or AgB, and inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 33 publications
0
20
0
Order By: Relevance
“…First, distinct studies showed that the 12 kDa subunit of AgB is a serine protease inhibitor with strong chemoattractant activity and with the ability to inhibit human neutrophil chemotaxis without altering either random migration or oxidative metabolism [41,42]. In agreement with the negative immunomodulatory role suggested for AgB on human neutrophils, when accidentally released hydatid fluid activates neutrophils, AgB could act as an interference antigen allowing the released protoscoleces to develop into secondary cysts [43].…”
Section: Immunomodulating Molecules: Role Of Antigen B and Of Other Nmentioning
confidence: 94%
“…First, distinct studies showed that the 12 kDa subunit of AgB is a serine protease inhibitor with strong chemoattractant activity and with the ability to inhibit human neutrophil chemotaxis without altering either random migration or oxidative metabolism [41,42]. In agreement with the negative immunomodulatory role suggested for AgB on human neutrophils, when accidentally released hydatid fluid activates neutrophils, AgB could act as an interference antigen allowing the released protoscoleces to develop into secondary cysts [43].…”
Section: Immunomodulating Molecules: Role Of Antigen B and Of Other Nmentioning
confidence: 94%
“…In agreement with the negative immunomodulatory role suggested for AgB on human neutrophils, when accidentally released hydatid fluid activates neutrophils, AgB could act as an interference antigen allowing the released protoscoleces to develop into secondary cysts [96]. We investigated the role of AgB in acquired immunity by evaluating AgB-driven Th1 and Th2 cytokine production by PBMC from patients with CE [9597].…”
Section: E Granulosus and Immune-modulating Moleculesmentioning
confidence: 99%
“…It has a molecular size of circa 8 kDa on sodium dodecyl sulfate polyacrylamide gel electrophoresis (SDS-PAGE) (Lightowlers et al, 1989;Shepherd and McManus, 1987) under reduced conditions. The function of AgB in the parasite's biology is not completely elucidated, but several studies have shown that the molecule may be involved in the modulation of the host immune response; for instance, as a protease inhibitor that inhibits neutrophil chemotaxis (Shepherd et al, 1991;Virginio et al, 2007), promoting a non-protective Th2 response by interfering with monocyte differentiation, and by modulating DC maturation (Kanan and Chain, 2006;Rigano et al, 2007). One study has suggested that AgB could be involved in the processes of lipid uptake or detoxification (Chemale et al, 2005).…”
Section: E Granulosus Antigen Bmentioning
confidence: 99%